2016
DOI: 10.4070/kcj.2016.46.6.791
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Angiotensin-II Type 1 Receptor Gene Polymorphism and Repolarization Parameters after a First Anterior Acute Myocardial Infarction

Abstract: Background and ObjectivesGenetic influence on T-wave peak to End (Tpe) time in patients with a first anterior acute myocardial infarction (AMI) is uncertain. A polymorphism in the angiotensin-II type 1 receptor (AT1R) gene was discovered recently. The polymorphism consists of an A or C variant, given three different possible genotypes: AA, AC, CC. The purpose of this study was to determine the effects of polymorphism of the AT1R gene polymorphism on Tpe after a first anterior AMI.Subjects and MethodsThe subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 23 publications
0
3
0
1
Order By: Relevance
“…The renin-angiotensin system is crucial regulating blood pressure and the development of CAD. Studies have found that polymorphisms in renin-angiotensin system-related genes, including AGT rs4762 ( 20 ), AGTR1 rs5186 ( 21 ), AGTR2 rs11091046 ( 22 ), KLK1 rs5517 ( 23 ), ACE rs1799752 ( 24 ), as well as ACE2 rs4646142 and rs1978124 ( 25 ), were associated with the risk of MI . The ACE gene insert/delete (I/D, rs1799752) polymorphism is the most extensively studied.…”
Section: Single-omics Approachesmentioning
confidence: 99%
“…The renin-angiotensin system is crucial regulating blood pressure and the development of CAD. Studies have found that polymorphisms in renin-angiotensin system-related genes, including AGT rs4762 ( 20 ), AGTR1 rs5186 ( 21 ), AGTR2 rs11091046 ( 22 ), KLK1 rs5517 ( 23 ), ACE rs1799752 ( 24 ), as well as ACE2 rs4646142 and rs1978124 ( 25 ), were associated with the risk of MI . The ACE gene insert/delete (I/D, rs1799752) polymorphism is the most extensively studied.…”
Section: Single-omics Approachesmentioning
confidence: 99%
“…Проведенные генетические исследования показали взаимосвязь генотипа СС гена AGTR1(A1166C) с толщиной задней стенки ЛЖ, межжелудочковой перегородки (МЖП) и ИММЛЖ в общей популяции (Jin Y. и соавт., 2012), а у пациентов с коронарной болезнью сердца генотипы АС и СС были ассоциированы с конечно-диастолическим и конечно-систолическими размерами и фракцией выброса ЛЖ (Mishra A. и соавт., 2015) [35,36]. Также была установлена взаимосвязь АС и СС генотипов гена AGTR1 (A1166C) с повышенным риском реполяризационных нарушений при ЭКГ (длительность и дисперсия интервала QT) у пациентов с острым инфарктом миокарда передней стенки ЛЖ (Ozturk O. и соавт., 2016) и CC генотипа -с увеличением риска развития жизнеугрожающих аритмий у пациентов с хронической сердечной недостаточностью [37,38]. Синергичное влияние генетического полиморфизма генов AGTR1 и CYP11B2 на развитие ГЛЖ может быть обусловлено тем, что альдостерон потенциирует гипертрофические эффекты ангиотензина II [39].…”
Section: на следующую на первую на предыдущую к содержаниюunclassified
“…Angiotensin II is the most potent vasoconstrictive and inflammatory component of the RAAS. Most of its pressor, inflammatory, and proliferative actions are regulated by AT1R which is expressed in the myocardium [8].…”
Section: Introductionmentioning
confidence: 99%